Some aspects of the ecophysiology of germination in Physalis philadelphica - Rivera Madrid, Renata; Garza Caligaris, Luz Elena; Rincón, Emmanuel (Instituto de Ecología, A.C., 1989)
This paper refers to the germination in Physalis philadelphica. Results show that seed germination occurs in a wide range of temperatura (13 to 40°C), presenting the optimum between 25 and 37°C with more than 80% of germination. The seeds are photoblastic, but this characteristic is inhibited with the increment of temperatura. The red/far red ratio needed to obtain high percentages of germination is over 0.9 at 30°C.